The Cost of Expanding Ethiopia’s Salt Iodization Program to Include Multiple Micronutrients - Katherine P Adams; Dawd Gashu; Elias Asfaw Zegeye; MG Venkatesh Mannar; Levente L Diosady; N Ananth; E Louise Ander (Current Developments in Nutrition)
Background: With near universal consumption of salt and technological advances that have made its fortification with multiple micronutrients feasible, salt has great potential for public health impact as a delivery vehicle for not only iodine but also multiple micronutrients. Decisions around modifying existing salt standards to include additional micronutrients should consider not only potential impacts but also stakeholder-specific costs. Objectives: We aimed to estimate the total and incremental cost of expanding Ethiopia’s salt iodization program to include folic acid (dual fortified salt), folic acid and vitamin B-12 (triple fortified salt), or folic acid, vitamin B-12, and zinc (quadruple fortified salt). Methods: We developed activity-based cost models to estimate salt fortification costs over a 10-y time horizon (2024–2033). Model assumptions and parameters were primarily based on interviews with Ethiopian stakeholders in industry and government and nongovernmental partners. Results: The estimated annual average per capita cost of Ethiopia’s existing salt iodization program was ∼$2.1 million (2021 US dollars) or ∼$7/metric ton (MT) of fortified salt (∼$0.02/y). Expanding the program to include folic acid, which could be sprayed onto salt along with the iodine, would increase the annual average per capita cost to ∼$2.5 million, or ∼$8.30/MT (∼$0.02/y). Annually, the costs of triple and quadruple fortified salt programs, which would require encapsulating the additional micronutrients as a solid premix to help ensure stability, were ∼$18 million (∼$59/MT; $0.13 per capita) and $19 million (∼$63/MT; ∼$0.14 per capita), respectively. Premix costs accounted for approximately half of the total cost of the iodized and dual fortified salt programs and ∼90% of triple and quadruple fortified salt. Conclusions: If Ethiopia considers modifying its existing salt iodization standard to include 1 or more additional micronutrients, there will be many important considerations, including costs and affordability. The cost estimates presented in this study can complement evidence of the potential for multiple fortified salt to reduce micronutrient deficiencies.